Female Consumer Buying Behavior toward Cosmetic Products in Pokhara, Nepal - Ranabhat, Deepesh; Sapkota, Pradeep; Timsina, Sangita; Ranabhat, Mala; Thapa, Roshani (KIC International Journal of Social Science and Management, 2024)
The pursuit of beauty and self-enhancement has been a central aspect of women's lives across cultures, with cosmetics playing a significant role in shaping consumer behavior. This study aimed to explore the factors influencing female buying behavior toward cosmetic products in Pokhara, focusing on variables such as brand loyalty, perceived product quality, social media influence, brand reputation, and personal values. Employing a descriptive and causal comparative research design, data were collected from 225 female respondents using structured questionnaires. Descriptive statistics, correlation analysis, and multiple regression techniques were utilized to analyze the data. The findings revealed that social media influence and personal values significantly impacted buying behavior, while brand loyalty, perceived product quality, and brand reputation showed positive correlations but lacked statistical significance. The study concludes that businesses can enhance female buying behavior by leveraging social media platforms and aligning marketing strategies with consumers’ personal values. Further research could delve into cultural and trend-based factors to provide deeper insights into the dynamics of female consumer behavior in the cosmetics industry.